Prevalence of dyslipidaemia and awareness of blood cholesterol levels among community-living people: results from the Longevity check-up 7+ (Lookup 7+) cross-sectional survey. Issue 6 (30th June 2018) - Marzetti, Emanuele; Calvani, Riccardo; Picca, Anna; Sisto, Alex; Tosato, Matteo; Martone, Anna Maria; Ortolani, Elena; Salini, Sara; Pafundi, Teodosio; Santoliquido, Angelo; Santoro, Luca; Bernabei, Roberto; et al.
Abstract : Objective: The aim of the present study was to investigate the prevalence of abnormal cholesterol levels and to explore awareness of cholesterol values in an unselected sample of community-living adults. Design: Cross-sectional survey. Setting: Exhibitions, malls and health promotion campaigns across Italy. Participants: 3535 community dwellers aged 18–98 years were enrolled between September 2016 and June 2017. Analyses were conducted in 3040 participants, after excluding 495 enrolees on cholesterol-lowering medications. Main outcome measures: Total blood cholesterol levels and awareness of cholesterol values. Results: Abnormal blood cholesterol values were found in 1961 (64.5%) of participants with no differences between genders (p=0.06). Among those who believed they had normal cholesterol levels, only 48% had values below 200 mg/dL. More than 40% had cholesterol values between 200 and 240 mg/dL, and around 10% had values >240 mg/dL. More than one-third of participants had not measured cholesterol in the last year. Among them, only 36% had normal cholesterol levels. Conclusions: Abnormal blood cholesterol is highly prevalent in our sample of Italian community dwellers, with less than half of participants being aware of their cholesterol levels.